Embodied cognition: So flexible as to be “disembodied”? - Ianì, Francesco (Consciousness and cognition, 2021)
This review aims to explore what I call the “Embodiment Cost Hypothesis” (ECH), according to which, when humans “embody” a part of the world other than their bodies, a measurable cost is detectable on their real bodies. The review analyzes experimental evidence in favor of the ECH by examining studies from different research fields, including studies of action observation (2), tool-use (3), rubber hand illusion (4), and full-body illusions (5). In light of this literature, this review argues that embodiment effects can profitably be seen as phenomena associated with both benefits (resulting from the embodiment of external objects/bodies) and costs (resulting from the disembodiment at various levels of the subject’s own body). Implications are discussed in relation to the ongoing debate on the embodied cognition (EC) approach.